Characteristics of Bituminous Coal Permeability Response to the Pore Pressure and Effective Shear Stress in the Huaibei Coalfield in China. (31st March 2019) - Zhang, Lei; Ye, Zhiwei; Huang, Mengqian; Zhang, Cun
Abstract : The coal permeability is known to be influenced by the pore pressure and effective stress in coal mines. In this study, the characteristics of the bituminous coal permeability response to the pore pressure and effective shear stress in the Xutuan coal mine in Huaibei Coalfield in China were investigated under different stress conditions. For this purpose, gas seepage tests with various stress levels were conducted via the original gas flow and displacement testing apparatus using bituminous coal samples from the Xutuan coal mine. The pore pressure effect on the permeability under different stress conditions was assessed by varying the pore pressure in coal samples and simulating different in situ stresses. The axial and radial pressures were controlled to study the response of coal permeability to the effective shear stress. The experimental results revealed that with an increase in pore pressure, the permeability of coal in different stress environments firstly drops and then rises. The permeability increased gradually with the effective shear stress, which trend became more pronounced when the effective shear stress exceeded zero. In case of the axial pressure exceeding the radial one, the cross shear slip was observed, for which the permeability of coal samples increased with the effective shear stress. In the opposite case, the separated shear slip was observed, with the reverse trend.